(untitled) (Journal of the College of Basic Education, 2023)
Praise be to God, and may blessings and peace be upon the best of God’s creation, our Prophet Muhammad and his family and companions. The condition is one of the methods that students have been interested in, as it is one of the constructive methods that are based on the suspension of two expressions in which the first is the cause of the second, and the failure of the first means that the second does not occur. And the verb condition sentence and the condition answer sentence. The condition is based on attachment and arrangement, and that can only be done by one of the condition tools. The conditional tools have the precursor of the conditional sentences, so all the conditional tools have the right to be at the beginning of the sentence, some of them are letters, some of them are names, and some of them are adverbs, and they are divided in terms of work on: deterministic and non-assertive tools, and they differ in their meanings, and their syntax. Each tool has its own meaning. The occurrence of (from) the conditionality is a starting point and the differences of scholars re The opinions of the scholars and their differences are presented in a report (from) the conditionality. If it is a starting point, then they have three opinions regarding that. Or the answer to the condition is the news, or the condition verb is the news. I mentioned that the reason for the disagreement in which the scholars had occurred was their disagreement in the first place regarding the meaning of the sentence, and our scholars did not agree on its meaning and did not specify it.The responses were presented to the first and second opinions, then showed that the third opinion, which is the opinion that Ibn Hisham favored and supported in his opinion, is that the verb of the condition alone is the news garding its knowledge were the focus of the research. And Praise be to Allah, the Lord of the Worlds